Design and Evaluation of anti-STEAP2 antibodies to treat aggressive Prostate Cancer - AI-MY CHI (2020)
Introduction: Prostate cancer is the second most frequent male cancer worldwide. Although prostate cancer is not always life-threatening when confined to the gland, the 5-year survival rate remains poor for men with advanced disease at approximately 30%. For such patients, there is an unmet need for patient-tailored drugs to improve their clinical management and quality of life, since current therapy options are accompanied with severe side-effects. The Six-Transmembrane Epithelial Antigen of the Prostate2 (STEAP2) is a cell surface protein highly expressed in advanced prostate cancer but not in the normal prostate. STEAP2 drives cancer invasive traits associated with prostate cancer progression in vitro and represents a promising drug target. The aim of this thesis was therefore to evaluate, whether STEAP2 is a viable drug target in vitro, with a focus on the application of antibodies (Abs) and Ab-Drug-Conjugates (ADCs), to treat advanced prostate cancer. Methods: Immunohistochemistry (IHC) analysis of tissue-microarrays (TMAs) containing 33 tissues across the human body was conducted to assess the normal tissue profile of STEAP2. Structural analysis of STEAP2 was performed to identify targetable regions for the use of Ab therapeutics. One commercial polyclonal anti-STEAP2 Ab (anti-STEAP2 pAb) was selected for proof-of-concept studies based on the ability to detect both linear and native STEAP2 by confocal microscopy and protein analysis in prostate cancer cells (PC3) and normal prostate epithelial cells (PNT2). The effect of the anti-STEAP2 pAb on cancer invasive traits was studied in PC3 and PNT2 cells. Receptor internalisation of STEAP2 was evaluated upon anti-STEAP2 pAb binding to confirm the suitability of the ADC technology by confocal microscopy. A polyclonal anti-STEAP2-monomethylauristatin-E (MMAE) ADC (anti-STEAP2 pADC) was produced to compare its effect on reducing the cell viability of PC3 cells versus the unconjugated anti-STEAP2 pAb alone. Monoclonal anti-STEAP2 Ab (anti-STEAP2 mAb) was generated by the hybridoma technology using Balb/C mice. The specificity of the mAbs to STEAP2 was analysed by ELISA, Western blot and confocal microscopy. Results: IHC/TMA analysis showed low STEAP2 protein levels in 33 different organs across the human body. Structural analysis of STEAP2 identified five targetable domains (Peptides1 - 5) specific to the extracellular loops1 - 3 (ECL1 - 3) of STEAP2. Peptide5/ECL3, „GWKRAFEEEYYRFY“, appeared as the most promising immunogen region and was used as the antigen for mAb development. Anti-pAb treatment reduced cancer cell migration, invasion and viability of PC3 cells and triggered receptor internalisation of STEAP2. The anti-STEAP2- pADC was 3-fold more efficient than the unconjugated anti-STEAP2 pAb in decreasing the cell viability at a dose of 100 µg/ml. Peptide5/ECL3 elicited a moderate immune response in Balb/C mice. Four anti-STEAP2 mAbs were developed and their specificity to STEAP2 was confirmed by ELISA. Conclusion: The low tissue expression profile of STEAP2 implies few off-target side-effects are likely to occur if STEAP2 is to be utilised as a future drug target. Peptide1 - 5 specific to the ECL1 - 3 of STEAP2 are potential antigen regions for future mAb development. When ECL3 was evaluated, the anti-STEAP2 pAb targeting this region was indeed capable of significantly reducing cancer invasive traits and triggered receptor internalisation in PC3 cells. Assessment of the anti-STEAP2 pADC demonstrated the potential utility of the ADC technology in the future. These promising findings highlight the therapeutic value of Ab-based strategies against STEAP2 to block cancer invasive traits. Evaluation of the four generated anti-STEAP2 mAbs indicated their specificity to STEAP2, albeit future validation is required. The in-vitro findings presented herein provide proof-of-concept, that supports STEAP2 as a viable drug target, with a focus on Abs and ADCs, prior to preclinical in-vivo studies for the treatment of patients with advanced prostate cancer.